Analysis of interregional industry linkage and economic distance in China: evidence from the mining industry. Issue 6 (1st February 2017) - Wang, Zhaohua; Sun, Junwei
ABSTRACT: The mining industry is an important sector of the national economy, which provides essential support for energy and other resources for economic development. Industrial linkage and economic distance are two different concepts in measuring the correlationship of different industries, in this article, we apply the model that combines both of them to analyse the industries significantly influence the mining industry. We find that electricity and heating industry, and the mining industry itself from forward linkages have greatly influenced the mining industry, and the industries from backward linkages affect mining industry are changing with industrial economic transformation. We also find resources can flow across several regions only after 2007, which means the role of geographical factors limiting long-range transportation of resources is weakening after 2007. And we explain how resources flow among various regions during 1997 ~ 2007. Based on the findings above, policy implications from the empirical results obtained are discussed.